Molecular Phylogenetic Variability of Fasciola gigantica in Iran - Saber RAEGHI; Soheila ROUHANI; Majid FASIHI HARANDI; Adel SPOTIN; Sahar GHODSIAN (Tehran University of Medical Sciences, 2019)
Background: Fascioliasis is one of important zoonotic disease caused by Fasciola gigantica and F. hepatica. The final hosts of this parasite are ruminants and humans. Iran is one of the endemic areas in the world, about six million people at risk of infection. The aim of this study was to identify and determine the genetic diversity of Fasciola species in cattle after distinguish of their species. Methods: One hundred and seventeen liver specimens collected from naturally infected cattle in 5 geographical regions in 2014-2017. Flukes stained with Hematoxylin-Carmine dye to examine for the existence of sperm within seminal vesicles. DNA was extracted from each individual, and ITS1, ND1and CO1 genes were amplified using specific primers. For discrimination of Fasciola species, ITS1 PCR-RFLP was used based on digestion pattern of RsaI enzyme. Genetic analyses and diversity and neutrality indices estimated by Dnasp5 based on NDI. Results: Six nonspermic and 111 spermic flukes were diagnosed. All of nonspermic specimens were F. gigantica and collected from South East, South West and North West of Iran. Genetic haplotype diversity has been observed in F. gigantica based on ND1. Fst value analysis showed that minimum and maximum genetic difference between Iranian F. gigantica with Bangladesh (Fst = 0.01414) and Egypt (Fst = 0.36653) respectively. Conclusion: It is the first report of existing of nonspermic Fasciola. High haplotype and nucleotide diversity could be due to ecological factors in life cycle, animal migration and coexisting of the final host of this parasite. Haplotype and nucleotide diversity of spermic F. gigantica in Iran and other countries in the world led to creating a variety of haplogroups.